Vancomycin Induced Thrombocytopenia in Sepsis Patient - Kaunang, Prisilia Rianni; Lantang, Eka Yudha; Siahaan, Waldemar (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Vancomycin is a widely used glycopeptide antibiotic for severe Gram-positive infections, yet it may cause rare but serious adverse effects such as vancomycin-induced thrombocytopenia (VIT), which is often under-recognized in critically ill patients. This study aims to describe a case of suspected VIT in a septic patient and to highlight the diagnostic challenges and clinical implications in intensive care settings. A case report method was applied, involving detailed clinical observation, laboratory monitoring, and evaluation of temporal relationships between drug exposure and hematologic changes. The patient, a 70-year-old male with multiple comorbidities and severe sepsis, developed a sudden and profound decline in platelet count following approximately one week of vancomycin therapy. Despite the presence of other potential causes of thrombocytopenia, including sepsis and disseminated intravascular coagulation, the rapid onset and severity of platelet reduction, along with its temporal association with vancomycin administration, strongly suggested an immune-mediated mechanism. The clinical course was further complicated by multiorgan failure and multidrug-resistant infections, ultimately leading to mortality. This case underscores the importance of early recognition of drug-induced thrombocytopenia, careful evaluation of differential diagnoses, and timely discontinuation of the offending agent. Increased awareness of VIT among clinicians is essential to reduce morbidity and improve outcomes in critically ill patients.